Field‐amplified sample injection in capillary electrophoresis with amperometric detection for the ultratrace analysis of diastereomeric ephedrine alkaloids. Issue 16 (August 2015) - Chen, Xiaoyan; Tang, Yanxia; Wang, Shaoyun; Song, Yunping; Tang, Fengxiang; Wu, Xiaoping; Escarpa, Alberto; Pumera, Martin
<x xml:space="preserve">Abstract</x> A coupling method of field‐amplified sample injection (FASI) CE with amperometric detection is developed for ultratrace analysis of ephedrine alkaloids stereoisomers. FASI was introduced by injecting electrokinetically the sample solution for 10 s into the capillary filled with highly conductive background electrolyte (BGE). The diastereomeric selectivity and the detection sensitivity were improved by using borate buffer of high ionic strength as BGE. Parameters affecting FASI and CE separation were investigated to achieve the optimal conditions. Four analytes were separated within 15 min using 200 mmol/L borate buffer (pH 9.5) and separation voltage of +18 kV, with detection potential at +1.0 V (vs. Ag/AgCl) and carbon disc electrode as working electrode. Excellent linearity was observed between peak current and concentration of analytes in the range of 0.1–100 ng/mL. The LODs (S/N = 3) for (−)‐ephedrine, (+)‐pseudoephedrine, (−)‐N‐methylephedrine and (+)‐N‐methylpseudoephedrine were 39.3, 54.9, 30.8, and 44.1 pg/mL, respectively. The proposed method was successfully applied to the determination of alkaloids in Ephedra sinica, with results agreed well with HPLC method. Mean recoveries of 102.1–109.7% and RSDs less than 6% were found. And the merits of high sensitivity and selectivity, as well as a simple and stable operation, have been demonstrated.